2008
DOI: 10.1080/14767050802034545
|View full text |Cite
|
Sign up to set email alerts
|

The change in concentrations of angiogenic and anti-angiogenic factors in maternal plasma between the first and second trimesters in risk assessment for the subsequent development of preeclampsia and small-for-gestational age

Abstract: The change in concentrations of angiogenic and anti-angiogenic factors in maternal plasma between the first and second trimesters in risk assessment for the subsequent development of preeclampsia and small-for-gestational age, The Journal of Maternal-Fetal & Neonatal Medicine, 21:5, 279-287, DOI: 10.1080 AbstractIntroduction. An imbalance between angiogenic and anti-angiogenic factors has been proposed as central to the pathophysiology of preeclampsia (PE). Indeed, patients with PE and those delivering small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
236
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(264 citation statements)
references
References 60 publications
21
236
2
5
Order By: Relevance
“…In contrast, a large nested case-control study within a cohort of nearly 30,000 pregnant women in Norway showed that low sFlt1 in first trimester predicted early onset preeclampsia [41]. Kusanovic et al also had confirmed that low sFlt1 in first trimester predicting preterm (as well as term) preeclampsia [43] and Erez et al [42]. Although after adjusting for BMI, age and nulliparity, this significance had disappeared.…”
Section: Soluble Fms-like Tyrosine Kinase-1mentioning
confidence: 88%
See 3 more Smart Citations
“…In contrast, a large nested case-control study within a cohort of nearly 30,000 pregnant women in Norway showed that low sFlt1 in first trimester predicted early onset preeclampsia [41]. Kusanovic et al also had confirmed that low sFlt1 in first trimester predicting preterm (as well as term) preeclampsia [43] and Erez et al [42]. Although after adjusting for BMI, age and nulliparity, this significance had disappeared.…”
Section: Soluble Fms-like Tyrosine Kinase-1mentioning
confidence: 88%
“…PIGF value is also low with pregnancy complications associated with a dysfunctional placenta (SGA, preeclampsia or both) [44]. Several studies have found that low PlGF concentrations in first trimester are also predictive factor for SGA, even in the absence of preeclampsia [40,42,47].…”
Section: Reference Pz (N) Gestational Week Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A third article demonstrates that the magnitude of change in the maternal plasma concentrations of anti-angiogenic and angiogenic factors is associated with the subsequent risk for the development of preterm and term preeclampsia as well as delivering an SGA neonate [56].…”
Section: The Role Of Angiogenic and Anti-angiogenic Factorsmentioning
confidence: 99%